The influence of gestational age at term on breastfeeding: a cohort study - Michelin, Nathallia Seródio [UNESP]; de Carvalho Nunes, Hélio Rubens [UNESP]; de Barros Leite Carvalhaes, Maria Antonieta [UNESP]; de Lima Parada, Cristina Maria Garcia [UNESP] (FapUNIFESP (SciELO), 2021)
Objective: To identify the effect of the category gestational age at term on breastfeeding in he first hour of life, the duration of exclusive breastfeeding, and practice of breastfeeding twelve months from birth. Method: Single cohort, with a one-year prospective followup of 541 children. A hierarchical analysis was performed, with models adjusted per Cox regression, considering critical p < 0.05. Results: During raw analysis there was a statistical difference on breastfeeding in the first hour of life (RR = 1.54; CI 95% = 1.12–2.12; p = 0.008). However, in the final analysis, there was no association between gestational age at term and breastfeeding in the first hour of life, duration of exclusive breastfeeding, and the practice of breastfeeding twelve months from birth. Secondarily, higher age and education, cesarean section, birth at private services, and the need for resuscitation were observed to have a negative influence. Duration of previous pregnancy favored breastfeeding in the first hour of life. Using baby bottle and pacifier was negative for breastfeeding in the first year of life. Conclusion: There was no association between the category gestational age at term and breastfeeding. The association of outcomes pointed out by the scientific literature have been confirmed.
Influencia de la edad gestacional a término en la lactancia materna: un estudio de cohorte
Influência da idade gestacional no termo sobre o aleitamento materno: estudo de coorte
Keywords: Breast Feeding; Feeding Behavior; Gestational Age; Maternal-Child Nursing; Term Birth